Development and characterization of novel microsatellite markers in Puccinia striiformis f.sp. tritici and their transferability in Puccinia species. Issue 2 (19th December 2019) - Savadi, Siddanna; Prasad, Pramod; Bhardwaj, Subhash Chander; Rathore, Ruchi; Sharma, Kiran; Lal Kashyap, Prem; Gangwar, Om Prakash; Kumar, Subodh
Abstract: Puccinia striiformis f.sp. tritici ( Pst ) and P. striiformis f.sp. hordei ( Psh ) causing stripe rust disease in wheat and barley, respectively, are two devastating phytopathogens. Microsatellite/simple sequence repeat (SSR) markers are increasingly being utilized for analysis of genetic diversity, diagnosis, population structure and possible migratory routes of plant pathogens. In the current study, novel polymorphic SSR markers were designed for Pst using the genomic sequences of PST‐78 isolate. A total of 1, 191 SSR motifs, comprising 30% each of di‐ and tri‐nucleotide type of repeats, 17% of penta‐nucleotide, 15% of tetra‐nucleotide and 8% of hexa‐nucleotide repeats, were detected through in silico scanning of PST‐78 genomic sequences. Polymorphism was detected by nine of the 50 designed SSRs (PsSSRs) in seven stripe rust pathotypes of wheat and barley. The mean number of alleles per SSR locus, mean polymorphism information content (PIC), mean heterozygosity, mean major allele frequency (MAF) and mean gene diversity were 2.33, 0.34, 0.33, 0.71 and 0.40, respectively. The dendrogram analysis suggested that newly developed PsSSR markers could distinguish stripe rust pathotypes based on their virulence phenotype. Further, the cross‐genera and cross‐species amplification test of these markers in 14 different rust pathotypes revealed that 9 PsSSRs are capable of amplification in Pst species infecting wild grass, followed by 6 PsSSRs in Pt, 3 PsSSRs in Pgt, 1 PsSSRs in Puccinia species on barberry and Melampsora lini . Thus, the transferability of PsSSRs to other species reduced with increasing genetic distance of target species. These newly designed SSR markers expand the available Pst SSR marker resources and allow better genetic studies.